The Gains and Pains of Financial Integration and Trade Liberalization : Lessons from Emerging Economies. - Bhattacharyya, Rajib (Emerald Publishing Limited, 2019)
Geared towards policy makers, researchers, academics, and business and management professionals, The Gains and Pains of Financial Integration and Trade Liberalization helps readers develop new theories and models for analysing the future trends in finance and trade-related issues.